Effects of Implicit Prosody and Semantic Bias on the Resolution of Ambiguous Chinese Phrases - Yu, Miao; Sommers, Brandon; Yin, Yuxia; Yan, Guoli (Frontiers in Psychology, 2019)
By manipulating the location of prosodic boundary and the semantic bias of the ambiguous “V+N1+de+N2” phrase, which is composed of one verb (V), one noun (N1), one functional word (de), and another noun (N2), this study investigated how prosodic boundary and the semantic bias affect the processing of temporary ambiguous sentences formed by the ambiguous phrase “V+N1+de+N2” through an eye movement experiment. We found the effect of prosodic boundary in the late processing stage and observed an interaction between prosodic boundary and the semantic bias of ambiguous phrases as well. The participants required more time for fixation and more regressions occurred when the meaning of the ambiguous phrase guided by prosodic boundary was inconsistent with context, especially when the ambiguous phrase was biased to the narrative-object phrase. This result suggests that prosodic boundary affects the processing of temporal ambiguous sentences and is influenced by the semantic bias of the ambiguous phrase. These findings provide further evidence from Chinese that indicate that implicit prosody plays a general role in language comprehension.